Therapeutic Neurointervention through Transradial Approach: Preliminary Experience from a Tertiary Care Center - Bhatia, Vikas; Kumar, Ajay; Wani, Mohd Yaqoob; Singla, Navneet; Prabhakar, Anuj; Karthigeyan, Madhivanan; Chauhan, Rajeev (Indian Journal of Neurosurgery, 2022)
Background The aim of this study was to assess the safety and feasibility of radial access for therapeutic neurointervention procedures.Methods The retrospective evaluation of 20 patients taken for therapeutic neurointervention through transradial access at our institute was done from July 2021 to April 2022.Results Therapeutic neurointervention procedures were attempted in 20 patients (age, 24–74 years; mean age, 48.4 years; 13 (65%) females using a transradial approach. The radial artery's mean diameter was 2.135 mm. The right radial access was taken in 18 (90%) cases. Indications for treatment were ruptured aneurysm in 13 (65%), mechanical thrombectomy in 5 (25%), flow diversion for a recanalized aneurysm in 1 (5%), and balloon occlusion test in 1 (5%) case. The procedure was successful through the transradial approach in 18 (90%) procedures. Failure was seen in two cases that were completed after conversion to the transfemoral approach. The reason for access conversion was a severe spasm in both cases. No significant access site complications were seen in the study cohort.Conclusion A radial access route is a promising approach for therapeutic interventions with a high success rate and minimal access site complications. Interventionists should get accustomed to this approach as primary or alternative access for neurointervention.
Keywords: aneurysm; coiling; transradial